2006
DOI: 10.1016/j.physleta.2006.08.051
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational and stochastic resonances in two coupled overdamped anharmonic oscillators

Abstract: We study the overdamped version of two coupled anharmonic oscillators under the influence of both low-and high-frequency forces respectively and a Gaussian noise term added to one of the two state variables of the system. The dynamics of the system is first studied in the presence of both forces separately without noise. In the presence of only one of the forces, no resonance behaviour is observed, however, hysteresis happens there. Then the influence of the high-frequency force in the presence of a low-freque… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 22 publications
1
32
1
Order By: Relevance
“…shown in Fig.9 for 3 values of E. It is found that as E decreases, the optimum SNR shifts towards the higher value of Z(2). This result has been reported earlier in the case of continuous systems also [10,12]. on ν 2 .…”
Section: Vr: Numerical and Analytical Resultssupporting
confidence: 88%
“…shown in Fig.9 for 3 values of E. It is found that as E decreases, the optimum SNR shifts towards the higher value of Z(2). This result has been reported earlier in the case of continuous systems also [10,12]. on ν 2 .…”
Section: Vr: Numerical and Analytical Resultssupporting
confidence: 88%
“…Noise is found to change the stability of nonlinear systems [23], induces vibrational and stochastic resonances [24] and fractal mean first passage limits [25]. Noise also reflects internal fluctuations [26,27] and phase transitions [28].…”
Section: Effect Of Gaussian Noise As Perturbationmentioning
confidence: 99%
“…The vibrational resonance phenomenon has been found in the double-well Duffing oscillator, [2][3][4] spatially extended, 5 excitable 6 systems, an overdamped bistable system, [7][8][9] and overdamped two-coupled anharmonic oscillators. 10,11 The effects of noise on vibrational resonance have also been ana-lyzed in certain systems. 7,12,13 Experimental evidence of vibrational resonance was found in a bistable vertical cavity surface emitting laser 13 and an optical system.…”
Section: Introductionmentioning
confidence: 99%